A study of the asymmetric shock reflection configurations in steady flows. (18th July 2017) - Tao, Yuan; Liu, Weidong; Fan, Xiaoqiang; Xiong, Bin; Yu, Jiangfei; Sun, Mingbo
Abstract : In this paper the asymmetric shock reflection configurations in two-dimensional steady flows have been studied theoretically. For an overall Mach reflection, it is found that the horizontal distance between both triple points in the Mach stem is related to the angles of two slip streams. Based on the features of the converging stream tube, several assumptions are put forward to perform better the wave configurations near the slip streams. Therefore, we present an analytical model here to describe the asymmetric overall Mach reflection configurations which agrees well with the computational and experimental results.